Wysheidskriteria vir die klassifikasie van psalms as wysheidspsalms - Burger, J. (Hervormde teologiese studies, 1991)
Criteria for identyfying wisdom psalms This article concerns itself with the identification of wisdom poems amongst the psalms in the Old Testament. Certain criteria for identifying wisdom psalms have already been determined through previous re search on the subject. The validity of these criteria is subsequently evaluated in the light of the generally accepted wisdom books namely Job, Proverbs and Ecclesiastes. This attempt generated an independent set of criteria (formal and pertaining contents) proposed for isolating wisdom psalms.